Prevalence of Bovine Brucellosis in Organized Dairy Farms, Using Milk ELISA, in Quetta City, Balochistan, Pakistan. (10th January 2011) - Shafee, Muhammad; Rabbani, Masood; Sheikh, Ali Ahmad; Ahmad, Mansoor din; Razzaq, Abdul
Abstract : A total of 200 milk samples from cattle (n = 86 ) and buffalo (n = 114 ) were evaluated using milk ring test (MRT) and indirect enzyme-linked immunosorbent assay (i-ELISA). The overall prevalence was found to be 3% and 8.5% in cattle and buffaloes using MRT and i-ELISA, respectively. The prevalence was 4.6% and 1.7% in cattle and buffalo using MRT, respectively, while i-ELISA exhibited 20% and 0% in cattle and buffalo, respectively. The prevalence was higher in government dairy farm, compared to privately owned dairy farm. This paper points out an alarming situation in the target area with respect to the public health significance.